Pengaruh Penghargaan Dan Sanksi Terhadap Kepuasan Kerja Pegawai Melalui Motivasi Kerja Internal Pada Dinas Kependudukan Dan Catatan Sipil Kota Medan - Nur Aiysah; Yulia Tiara Tanjung; Sudiaman Sudiaman (Departement of Mathematics Education, 2023)
This research aims to determine the influence of rewards on work motivation, the influence of sanctions on work motivation, the influence of rewards on job satisfaction, the influence of sanctions on job satisfaction and the influence of rewards and sanctions on work motivation and the job satisfaction of Medan City Population and Civil Registry Office employees. This research uses two dependent variables, namely rewards and sanctions, an intervening variable, namely job satisfaction, and an independent variable, namely work motivation., the effect of rewards on job satisfaction, the effect of sanctions on job satisfaction and the effect of rewards and sanctions on work motivation with job satisfaction of employees of the population and civil registration office of the city of Medan. This study uses two dependent variables, namely rewards and sanctions, intervening variables, namely job satisfaction and independent variables, namely work motivation. The data in this study were collected through distributing questionnaires to 40 employees at the population and civil registration office of the city of Medan as a research sample. The sampling technique used is non-probability sampling. The data analysis method used is quantitative analysis, namely validity test, reliability test, classical assumption test consisting of normality test, multicollinearity test and heteroscedasticity test, multiple linear regression analysis, hypothesis testing consisting of t test, F test and R2 test. Based on data analysis, the results showed that the indicators in this study were valid and reliable. In the classical assumption test, the data is normally distributed, there is no heteroscedasticity and multicollinearity. In the hypothesis test in the t test it is known that the award variable has a significant effect on work motivation, the sanction variable also has a significant effect on work motivation. In the F test it is known that awards and sanctions jointly affect work motivation. In the R2 test it is known that the award variable has a significant effect on work motivation, the sanction variable also has a significant effect on work motivation. In the F test it is known that rewards and sanctions jointly affect work motivation. In the R2 test it is known that the magnitude of the effect of rewards and sanctions on job satisfaction is 63.6%. While the remaining 36.4% is influenced by other factors outside the award and sanction variables.